Unbound and Underground: Chile's Ergo Sun Project from the Dictatorship to the Digital Era - Cardone, Resha (2014)
Cardone wrote chapters of a book manuscript and submitted two related articles to peer reviewed journals. She also transcribed and edited a scholarly interview, presented portions of book project at conference and traveled to site of book topic for on-ground research. Accomplishments are different than outlined in original proposal. The report describes project issues and results.
Keywords: dept.wll; faculty_collection; sabbatical_report